Local cerebral neurofilament light chain during acute stage is associated with clinical outcomes in stroke patients receiving endovascular thrombectomy - Kunxin Lin; Youliang Wang; Wenlong Zhao; Yiru Zheng; Xiaohua Sun; Ling Fang; Ying Fu; Ning Wang; Qianqian Lin (BMC Neurology)
Abstract Background Prediction of stroke outcomes is challenging due to limited predictive properties of clinical and radiological variables. We aimed to investigate whether local cerebral neurofilament light chain (NfL) could provide additional prognostic value. Methods We prospectively enrolled 110 consecutive patients with large vessel occlusion of the anterior circulation who underwent endovascular thrombectomy (EVT). We collected two different arterial blood samples during EVT: (1) Local: the region of the occluded vascular compartment; (2) Systemic: femoral artery. We used ultrasensitive single-molecule array assay to measure NfL levels, compare systemic and local NfL levels and explore the association of systemic and local NfL with imaging markers and clinical outcomes. Results Of the 220 blood samples from the 110 patients who received EVT, the local NfL levels was significantly lower than system levels. Compared with the lower level of local NfL, patients with higher local NfL were more likely male (74.5% vs. 54.5%, p = 0.017), had lower rate of intravenous thrombolysis (14.5% vs. 30.9%, p = 0.041), higher percentage of non-cardioembolic subtype (67.3% vs. 47.3%, p = 0.045). Neither system or local NfL levels correlated with baseline clinical-radiological variables including stroke severity, brain ischemic injury and collateral status. High local NfL could independently predict mortality (OR, 2.431; 95% CI, 1.099–5.378, p = 0.028) and functional outcome towards worse outcome at 90 days (OR, 2.596; 95% CI, 1.267–5.312, p = 0.009) after multivariable regression analysis. Conclusions Our study suggested that elevated baseline local NfL accumulated in the ischemic vasculature might be a promising predictor for increased adverse clinical outcome of patients receiving EVT.